Nanomaterials for the Local and Targeted Delivery of Osteoarthritis Drugs. (8th May 2012) - Chinnagounder Periyasamy, Parthiban; Leijten, Jeroen C. H.; Dijkstra, Pieter J.; Karperien, Marcel; Post, Janine N.
Abstract : Nanotechnology has found its potential in every possible field of science and engineering. It offers a plethora of options to design tools at the nanometer scale, which can be expected to function more effectively than micro- and macrosystems for specific applications. Although the debate regarding the safety of synthetic nanomaterials for clinical applications endures, it is a promising technology due to its potential to augment current treatments. Various materials such as synthetic polymer, biopolymers, or naturally occurring materials such as proteins and peptides can serve as building blocks for adaptive nanoscale formulations. The choice of materials depends highly on the application. We focus on the use of nanoparticles for the treatment of degenerative cartilage diseases, such as osteoarthritis (OA). Current therapies for OA focus on treating the symptoms rather than modifying the disease. The usefulness of OA disease modifying drugs is hampered by side effects and lack of suitable drug delivery systems that target, deliver, and retain drugs locally. This challenge can be overcome by using nanotechnological formulations. We describe the different nanodrug delivery systems and their potential for cartilage repair. This paper provides the reader basal understanding of nanomaterials and aims at drawing new perspectives on the use of existing nanotechnological formulations for the treatment of osteoarthritis.